UPAYA STARBUCKS CORP. DALAM MENCIPTAKAN GREEN INVESTMENT DI PROVINSI PAPUA DAN PAPUA BARAT - Ririen Ingrid, (2022)
The provinces of Papua and West Papua have abundant of natural resources, therefore the Indonesian government wants to improve the agricultural, plantation, and maritime sectors, especially in the coffee plantation sector. One way to improve the plantation sector is to open cooperation on the Green Investment program, which is expected to run effectively and be environmentally friendly. Therefore, this study discusses the efforts made by Starbucks in the Green Investment program held by the Indonesian government in Papua and West Papua Provinces. The problems raised in this study can be answered by using descriptive qualitative methods and research techniques through interviews, observations, and literature studies to analyze the topics raised. The analysis process of this research was carried out using the theory and concept of Multi-National Corporations (MNC) and Green Investment (GI). The results of the study explained that the implementation of the Green Investment program has been running, but it has not been optimal because it is hampered by the Covid-19 pandemic, even so, Starbucks can help in improving the plantation sector in Papua and West Papua Provinces through investments made in an environmentally friendly manner and based on environmental, social, and governance principles contained in ESG.